Improving Institutional Governance: A Need to Embrace Mindfulness, Selflessness and Compassion in Leadership - Oribu, W. S.; Chidiebele, E. J. O. (Archives of Business Research, 2025)
The purpose for the creation of institutions world over is to improve the welfare of the people as well as sustainability in the respective communities. In order cultivate truly thriving institutions, especially in Sub-Saharan Africa, there is need to re-look at what is actually ailing leadership these countries. In this paper we will explore what is actually required in a leader in order to understand what matters to the people they are leading in order to achieve the institutional objectives. It is obvious that everybody wants to be happy and to live a meaningful live in order to contribute to the well-being of others for sustainability. It is worth that that institutions like the United Nations Development Program (UNDP) was formed to work with individual countries in eradicating poverty while protecting the planet by helping countries develop strong policies, skills partnerships and institutions in order to sustain their progress. Even with the UNDP guidelines most institutions, organizations and initiatives have failed in achieving their set objectives thus becoming unsustainable. The failure to achieve set objectives has mainly been linked to issues to do with governance. In this article, we set to examine the role of Mindfulness, Selflessness and Compassion (MSC) in enhancing institutional governance. The review recommends the adoption of the MSC as a new philosophy in governance. This philosophy may be used to measure the levels of governance in institutions by examining the mindfulness, Selflessness and Compassion in the institutional leadership.